Draft Annual Plan 1982-83 Himachal Pradesh - Planning Commission (Planning Commission, 1982)
It would be very clear from the above data that the area under all major categories of crops has remained almost static during 1971—79 period. However, the area under pulses decreased in the last year of reporting by about 1.8 per cent. A better view of agricultural development can be had from the indices of agricultural production and productivity.
Planning Department, Himachal Pradesh